Hispanic America in Linguistic and Regional Studies: New Educational Encyclopedia - M. M. Raevskaya (Ибероамериканские тетради)
Book Review: E.V. Astakhova, Yu.V. Davtyan, E.V. Kriukova. Spanish-speaking countries of Latin America and the Caribbean: national images. History. Culture. Language. Textbook on linguistic and regional studies / Ed. by V. Iovenko. M.: Prometey, 2024. — 460 p. This book gives an insight into the history, politics, culture and art of 19 Spanishspeaking countries of Latin America and the Caribbean through the lens of the Spanish language. The aim of the book is to help train and develop linguistic and cultural skills. It contains original texts, creative exercises and video materials (virtual excursions, songs, fragments of fiction films and documentaries) with digital codes attached. Each unit dedicated to a certain country focuses on national varieties of the Spanish language, historical figures and fictional characters, cuisine, traditional clothing, as well as facts about the relations between the countries and Russia. The book is innovative and is intended for those who study Spanish in various educational institutions and for anyone interested in the past and present of Spanish-speaking countries in Latin America and the Caribbean.